A field study for assessing risk-contingent credit for Kenyan pastoralists and dairy farmers - Shee, Apurba; Turvey, Calum G.; Woodard, Joshua (Emerald Publishing Limited, 2015)
The purpose of this paper is to assess the feasibility of risk-contingent credit (RCC) by presenting an experimental and participatory game designed to explain the concept of RCC to Kenyan pastoralists and dairy farmers. The paper investigates the uptake potential of RCC through qualitative assessment of field experiments and focus groups.– The paper presents a method of community engagement through a participatory game played in a series of Focus Group Discussions (FGDs). The paper also presents theoretical justification of RCC in credit market structure.– The game effectively explains the concept and mechanism of RCC by reflecting local situation and production potential. Participatory exercises within focus group discussions indicate that there exists a strong interest and support for RCC.– The methodology described in this paper can be used in extension programs for promoting innovative rural microcredit in developing countries but should be modified according to the local production and associated weather and market risks.– Micro-insurance and credit program delivery can be improved by the innovative approach of community engagement for explaining financial products.